Economic knowledge in the content of its geographical and economic school education (Pedagogy of Higher and Secondary Education, 2014)
Lyulkova Yu. N. Economic knowledge in the content of its geographical and economic school education.The articledefines the place ofeconomic knowledgein the content ofits geographical and economiceducation.Determined that theeconomic knowledgeto be understoodas a system ofideas, concepts andterms, facts, displaying patterns, laws and theories, philosophical ideasthat form therelationship between the individualtodifferent phenomenaof socio-economic and public life.
Keywords: economic knowledge; school geography course; school economics course; subject competence; economic competence; geographic competence